(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article, the author writes about the problem of general description to the operating normative legal acts in a sphere fuel - power complex in Republic of Kazakhstan, problems sent to the decision related to energy efficiency and energy-savings. The realization of targeted state energy conservation policy, ensure energy security of our country. The essence of this policy is to ensure a stable population and the economy with energy, more efficient use of energy resources. Energy saving today is a very topical and multifaceted problem. Since energy is one of the main sources of livelihood of our economy, needs a focused and integrated approach to solving the problem of energy conservation and energy efficiency. Key words: energy, energy efficiency, energy-savings, proceeded in energy sources, energy consumptions.